2023
DOI: 10.1002/advs.202300897
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Osteopontin‐Integrin β3 Signaling in Infrapatellar Fat Pad Attenuates Osteoarthritis in Mice

Abstract: The knowledge of osteoarthritis (OA) has nowadays been extended from a focalized cartilage disorder to a multifactorial disease. Although recent investigations have reported that infrapatellar fat pad (IPFP) can trigger inflammation in the knee joint, the mechanisms behind the role of IPFP on knee OA progression remain to be defined. Here, dysregulated osteopontin (OPN) and integrin 𝜷3 signaling are found in the OA specimens of both human and mice. It is further demonstrated that IPFP-derived OPN participates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 73 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Dai et al found that OPN and integrin β3 were upregulated in the infrapatellar fat pad (IPFP) and calcified cartilage in OA mice as well as in humans and that IPFP-derived OPN contributed to cartilage degeneration, subchondral bone remodeling and IPFP fibrosis via OPN–integrin β3 signaling. Their study also showed that intra-IPFP injection of RGD-nanogel/siRNA Cd61, which specifically targeted the IPFP cells expressing OPN receptors, effectively reduced the expression of integrin β3 and attenuated OA progression in mice [ 107 ]. Luo, W. et al also reported that OPN, CD44 and HA synthase 1 (HAS1) were highly expressed in OA cartilage and chondrocytes, and OPN upregulated the expression of HAS1 and increased the anabolism of the synthesis of ECM components such as hyaluronic acid (HA) in cartilage through CD44 protein expression in OA mice, thereby inhibiting OA progression.…”
Section: Immunoregulatory Roles Of Opn In Diseasesmentioning
confidence: 99%
“…Dai et al found that OPN and integrin β3 were upregulated in the infrapatellar fat pad (IPFP) and calcified cartilage in OA mice as well as in humans and that IPFP-derived OPN contributed to cartilage degeneration, subchondral bone remodeling and IPFP fibrosis via OPN–integrin β3 signaling. Their study also showed that intra-IPFP injection of RGD-nanogel/siRNA Cd61, which specifically targeted the IPFP cells expressing OPN receptors, effectively reduced the expression of integrin β3 and attenuated OA progression in mice [ 107 ]. Luo, W. et al also reported that OPN, CD44 and HA synthase 1 (HAS1) were highly expressed in OA cartilage and chondrocytes, and OPN upregulated the expression of HAS1 and increased the anabolism of the synthesis of ECM components such as hyaluronic acid (HA) in cartilage through CD44 protein expression in OA mice, thereby inhibiting OA progression.…”
Section: Immunoregulatory Roles Of Opn In Diseasesmentioning
confidence: 99%
“…When chondrocytes are subjected to abnormal mechanical stimulation, such as overloading or joint injury, their metabolic balance is altered, leading to matrix loss and tissue degeneration, which can lead to osteoarthritis (OA) ( 4 , 5 ). OA is one of the most common and diverse degenerative diseases with complex pathogenesis that affects all joint tissues, characterized by cartilage degeneration, osteophyte formation, meniscal degeneration, subchondral bone remodeling, joint inflammation and fibrosis of the infrapatellar fat pad ( 6 12 ). The main clinical manifestations of OA patients are AC degeneration, subchondral bone sclerosis, synovitis, osteophyte formation, joint pain and disability ( 13 ).…”
Section: Introductionmentioning
confidence: 99%